2008
DOI: 10.1136/bjo.2008.138867
|View full text |Cite
|
Sign up to set email alerts
|

Stanford University Network for Diagnosis of Retinopathy of Prematurity (SUNDROP): 12-month experience with telemedicine screening

Abstract: The SUNDROP telemedicine screening initiative for ROP has proven to have a high degree of sensitivity and specificity for identification of referral warranted disease. These results indicate that telemedicine may improve accessibility of ROP screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 28 publications
1
42
1
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14] The RetCam imaging system (Clarity Medical Systems, Inc, Pleasanton, CA) has been employed in other aspects of pediatric ophthalmic medical and surgical care and has the potential to be used in telemedicine-based ROP care of premature infants. The purpose of our study was to demonstrate the feasibility of telemedicine screening for ROP, especially in identifying infants that require laser treatment.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] The RetCam imaging system (Clarity Medical Systems, Inc, Pleasanton, CA) has been employed in other aspects of pediatric ophthalmic medical and surgical care and has the potential to be used in telemedicine-based ROP care of premature infants. The purpose of our study was to demonstrate the feasibility of telemedicine screening for ROP, especially in identifying infants that require laser treatment.…”
mentioning
confidence: 99%
“…From a medical perspective, retinal imaging may become important, because published studies have demonstrated that the accuracy and consistency of plus disease diagnosis are imperfect, even when performed by recognized experts [27,28]. Previous studies have demonstrated that agreement between ophthalmoscopic and telemedical ROP examination modalities is high, even when images are captured by a trained neonatal nurse, and that telemedicine may actually be more accurate in some cases [9][10][11][12][13][14][15][16][17]. Therefore, from a medicolegal perspective, imaging may become important as a mechanism for objective documentation of examination findings.…”
Section: Discussionmentioning
confidence: 99%
“…This has potential to address many of the existing limitations of ROP care, and has become more realistic with the increasing availability of wide-angle digital retinal imaging devices. Using these cameras, telemedicine has been shown to have high accuracy and reliability for ROP diagnosis [9][10][11][12][13][14][15][16][17], and to be possibly more cost-effective than standard ophthalmoscopy for disease management [18,19]. However, no previous research to our knowledge has formally examined the acceptability of telemedicine to infants' families.…”
mentioning
confidence: 99%
“…Several feasibility studies demonstrate the enormous usefulness of the technology which includes the communities living in rural and remote areas [53][54][55][56][57]. However, our recent literature search found only a few telemedicine screening program [58,59]; both showed very promising results on AMD screening through telemedicine.…”
Section: Telemedicine For Amd Screeningmentioning
confidence: 99%